اقتراح صيغة للعلاقة بين تحسين دقة القياس والموثوقية في الشبكة الجيوديزية - فحصة, إياد (Latakia University Journal -Engineering Sciences Series, 2016)
يقدم البحث الصيغة الموسّعةً لعلاقة تحسين دقة القياس (المقدّمة من العالم Otrenbski )، والتي تشمل الشبكات الجيوديزية المرتبطة أوالحرة، مع قياسات مرتبطة أو غير مرتبطة، والتي يتم معالجتها وفق نظرية التربيعات الصغرى. بالإضافة إلى تحسين الدقة العام (Global) يعطي البحث صيغةً إضافيةً تأخذ بالإعتبار تحسين الدقة المحلي الخاص بكل قياسٍ(تحسين الدقة المحلي). وتمَّ البرهان على صحة الصيغة المقترحة بالإعتماد على المصفوفة الجامدة ( Idempotent Matrix ).بالإضافة إلى المفهوم العام لموثوقية الشبكة الجيوديزية المبين في المراجع الجيوديزية، يعطي البحث صيغةً للعلاقة بين تحسين دقة القياس وإحدى ميزات الموثوقية الداخلية (المقدمة من Pelzer)، والمستخدمة في تقييم القياسات الجيوديزية. يكشف البحث ويعطي المؤشرات الرياضية لتفاعل نموذج المعالجة الرياضية مع حدوث الأغلاط في القياسات الجيوديزية.Research offers expanded version of the relationship to improve measurement accuracy (provided by Otrenbski), which include correlated or free geodetic networks, with correlated or incorrelated observations, which are processed according to the Least Square theory. In addition to enhancing the Global accuracy, Research gives additional formula takes into consideration the enhancement of each observation (local precision). the validity of the proposed formula was proved depending on the Idempotent matrix.In addition to the general concept of the reliability of geodetic network (described in literature), Research gives the formula of the relationship between improvement of measurement accuracy and one of internal reliability features (provided by Pelzer), and used in the evaluation of geodetic measurements. Research find and gives the basic mathematical indicators of the interaction of processing model with the occurrence of errors in geodetic measurements.